Community health workers for mental health care in refugee camps: a scoping review - Rasha Istaiteyeh; Wael K. Al-Delaimy (International Journal for Equity in Health)
Abstract Objectives In recent years, countries in the Middle East and North Africa (MENA) region have seen a rise in immigration, driven by global conflicts, leading to increased prevalence of physical and mental health issues among refugees. This places significant demands on both refugees and healthcare professionals encountering them in various situations. The analysis considers the social and psychological implications of relying on specialized trainers versus the refugees themselves to determine the most effective and sustainable method for providing mental health support in challenging refugee camp environments. Methods This article uses a scoping review methodology to compare the impact of two approaches for addressing mental health needs in refugee camps. Drawing upon previous studies, the research investigates the effectiveness and sustainability of recruiting external experts versus empowering refugees as mental health trainers within their communities. Results The analysis suggests that in refugee camps, empowering refugees as mental health trainers within their communities yields more sustainable and culturally appropriate mental health support compared to recruiting external experts. This approach fosters community resilience and addresses the unique social and psychological needs of refugees in challenging camp environments. Conclusion Ultimately, this analysis demonstrates the context-specific nature of health interventions in refugee camps. Empowering refugees as mental health trainers emerges as a promising approach to addressing mental health needs sustainably and effectively within these environments.